Ethical dilemmas in pharmacogenomics - Κορδόνης (Thomas Kordonis) Θωμάς (Bioethica, 2018)
In the present article I will depict some of the emerging controversies that are expected to be of serious concern in the developing field of pharmacogenomics. Pharmacogenomics is the branch of genetics concerned with determining the likely response of an individual to therapeutic medications. The first upcoming issue is the voluntary agreement of the patients, concerning the research of their genome, that is also reflected in their relatives, as well as in their wider social group (s). Secondly, the great financial costs of pharmacogeonomic therapies is most likely to lead to new social inequalities or upsurge the existing ones in commodity of health. Furthermore, this will possibly lead to more group minorities, based on the rarity of some alleles among individuals and their following response to the applied medication. As for cognitive functions, pharmacogenomics seems to be a great challenge for the enhancement of both cognitive dysregulation in patients and intellectual ability in healthy individuals. Consequently, this will lead to an unbridgeable gap between the users and nonusers of newer medications regarding their intellectual abilities, that are unachievable by normal training of physical abilities. Last but not least, l will refer to whether or not genetic data regard strictly confidential personal data, not allowed to be published, despite of possible social benefit and to what extent their carrier has the right of ignoring it.